(untitled) (Research, Society and Development, 2022)
The study aims to build prospective scenarios on access to water by the rural population in the municipality of Cubati-PB, Seridó Oriental Paraibano. The limited access to water in the northeastern semi-arid region, given the situation of the population historically affected by drought in environmentally vulnerable areas, produces aggravating social, environmental and economic effects, especially in rural areas, which are reflected in the significant inequalities that exist within the region, such as difficulty in accessing potable water in a minimum quantity acceptable for human use. The research methodology used was the partial application of the method proposed by Marcial and Grumbach (2000). Data collection was carried out through on-site observation, informal conversations, photographic records and application of semi-structured interviews to choose the preliminary variables with an impact on access to water in the last ten years and application of questionnaires through Google Forms to choose the events that will impact the system studied in the next five years. It was also used to fill in the cross-impact matrix and choose the variables that occur in each of the scenarios: most likely, trend and ideal. It is concluded that the challenge in the process of democratizing access to water in the service of low-income families in rural communities in the northeastern semi-arid region demands decentralization of water supply, adequate management of water use in periods of drought and water planning with the participation of different social actors to guarantee priority access and multiple uses of this natural resource.